Estabilidade de órbitas congeladas em torno de satélites planetários utilizando o sistema hamiltoniano na forma normal - Santos, Josué Cardoso dos [UNESP] (2014)
This work seeks to formulations of analytical models and the development of computer programs to perform a search for stable orbits around planetary satellites that maybe helpful in planning space missions to be conducted to study these celestial bodies. The study takes into account artificial satellite orbits around planetary satellites under the influence of the third body pertubation (gravitational attraction of Jupiter) and the pertubations due to non-uniform distribution of mass (J2 and J3) of the main (central) body ... (Complete abstract click eletronic access below)